Environmental Fiq'h Paradigm on the Concept of Green and Blue Economy in Goals - Latifah, Eny (International Journal of Sustainability in Research, 2023)
Fiqh al-bì'ah is the regulation of Islamic legal norms that regulate human behavior and actions related to environmental conservation. Likewise with the green economy and blue economy, it is a code of economic behavior that must be maintained and preserved. The purpose of this research is to find out the concept of fiqh al bi'ah in the concept of green and blue economy in realizing sustainable development. The research method used is descriptive qualitative. type of library research by collecting and analyzing data sources from information in answering existing problems of inaccordance with the facts. The results of the study show that Fiqh al-bì'ah in the Maslahah- based concept of green economy and blue economy regulates the principles of good-bad or halal-haram which will become a benchmark for evaluating human actions towards the environment both on land, sea and water in the economy, so that in this way, Muslims will be able to present a religious approach that is based on the Qur'an, Hadith, Ijtihad and Qiyas in looking at environmental issues in orde